Attendance Recognation by Using Smart Meter Based On IoT Study Case : FST UIN Jakarta - Feri Fahrianto; Hendra Bayu Suseno; Alfatta Reza (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2019)
State Islamic University Syarif Hidayatullah Jakarta as rapidly growing university toward world-class research university placed in the edge of Jakarta has academic information centre running by Pustipanda (The Center of Information Technology and Database). The acadmic information system (AIS) has been used for recording an academic activity in university for almost a decade, this information system has a functionality for detecting the lecturer attandancity, but the attendance system needs to be input by admin. In this research, the system to detect attendancity from lecturer is build and synchronize to universisty academic information system. Internet of Things, based on ITU-T 2015, some objects are able to transmit data among object by using Internet connection. It means by this technology the Internet used has been widely changed, from human to machine communication now also become machine-to-machine communications. By using this technology a small object or device is able to implement into electrical system to detect an activity occured in the room. Things implemented in the room are able to monitor which electronic device is active and motion of moving objects, also the position of objects. The communication connection between smart phones and acces point in the class room is also monitored in order to identify the lecturer identity.